Spanish is better than English for discriminating Portuguese vowels: acoustic similarity versus vowel inventory size - Elvin, Jaydene; Escudero, Paola; Vasiliev, Polina (Frontiers in Psychology, 2014)
Second language (L2) learners often struggle to distinguish sound contrasts that are not present in their native language (L1). Models of non-native and L2 sound perception claim that perceptual similarity between L1 and L2 sound contrasts correctly predicts discrimination by naïve listeners and L2 learners. The present study tested the explanatory power of vowel inventory size versus acoustic properties as predictors of discrimination accuracy when naïve Australian English (AusE) and Iberian Spanish (IS) listeners are presented with six Brazilian Portuguese (BP) vowel contrasts. Our results show that IS listeners outperformed AusE listeners, confirming that cross-linguistic acoustic properties, rather than cross-linguistic vowel inventory sizes, successfully predict non-native discrimination difficulty. Furthermore, acoustic distance between BP vowels and closest L1 vowels successfully predicted differential levels of difficulty among the six BP contrasts, with BP /e-i/ and /o-u/ being the most difficult for both listener groups. We discuss the importance of our findings for the adequacy of models of L2 speech perception.